2004
DOI: 10.1051/0004-6361:20040992
|View full text |Cite
|
Sign up to set email alerts
|

The structure of radiative shock waves

Abstract: Abstract. We considered the structure of steady-state plane-parallel radiative shock waves propagating through the partially ionized hydrogen gas of temperature T 1 = 3000 K and density 10 −12 g cm −3 ≤ ρ 1 ≤ 10 −9 g cm −3 . The upstream Mach numbers range within 6 ≤ M 1 ≤ 14. In frequency intervals of hydrogen lines the radiation field was treated using the transfer equation in the frame of the observer for the moving medium, whereas the continuum radiation was calculated for the static medium. Doppler shifts… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 25 publications
1
29
0
Order By: Relevance
“…This result is quite consitent with high resolution spectroscopic observations of the strong hydrogen emissions in Mira, W Virginis, and RV Tauri stars (see references in Fadeyev & Gillet 2004). The redshifted emission component, if we take the infalling motion of the high atmosphere into account, comes from photodeexcitations occurring in the radiative precursor just ahead of the discontinuous jump, while the gas producing the blueshifted emission component is located in the hydrogen recombination zone of the wake.…”
Section: The Shock Associated To the "First Apparition" Of Hα Emissionsupporting
confidence: 83%
See 4 more Smart Citations
“…This result is quite consitent with high resolution spectroscopic observations of the strong hydrogen emissions in Mira, W Virginis, and RV Tauri stars (see references in Fadeyev & Gillet 2004). The redshifted emission component, if we take the infalling motion of the high atmosphere into account, comes from photodeexcitations occurring in the radiative precursor just ahead of the discontinuous jump, while the gas producing the blueshifted emission component is located in the hydrogen recombination zone of the wake.…”
Section: The Shock Associated To the "First Apparition" Of Hα Emissionsupporting
confidence: 83%
“…This width is several times smaller than those taking place in Mira, W Virginis, and RV Tauri stars (Fokin 1991). Fadeyev & Gillet (2004) found that the Doppler shift in Balmer emission lines is roughly one third of the shock front velocity V shock in the frame of the observer for gas densities of 10 −12 g cm ≤ ρ 1 ≤ 10 −9 gm cm. The upstream Mach numbers range within 6 ≤ M 1 ≤ 14 and a preshock temperature of T 1 = 3000 K,…”
Section: The Shock Associated To the "First Apparition" Of Hα Emissionmentioning
confidence: 70%
See 3 more Smart Citations